2021
DOI: 10.3390/pathogens10111519
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Production of Th1/Th2 Cytokines in Peripheral Blood Mononuclear Cells and Neutrophils by Hepatitis C Virus Infection in Chronically Infected Patients

Abstract: This study investigated the influence of Hepatitis C virus (HCV) infection on the cytokine production profiles of the peripheral blood monoculear cells (PBMC) and neutrophils in chronically naïve HCV-infected patients. Seventy-five genotype-4 naïve HCV-infected patients (HCV+) and healthy subjects (HCV−) were enrolled. The neutrophils and the PBMC were separated by density gradient sedimentation and stimulated with a mitogen. The culture supernatants were evaluated for levels of IFN-α, IFN-γ, IL-2, IL-4, IL-5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…to be significantly increased compared with younger individuals. 54,55 This also agrees with previous studies, where increased cytokines of Th1 response 56,57 and IP-10 58 were also observed in CHC patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…to be significantly increased compared with younger individuals. 54,55 This also agrees with previous studies, where increased cytokines of Th1 response 56,57 and IP-10 58 were also observed in CHC patients.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, elevated concentrations of the pro‐inflammatory cytokines IL‐1β, IL‐2, IL‐6, IL‐8, and TNF‐α were found, cytokines that during normal healthy aging have been shown to be significantly increased compared with younger individuals 54,55 . This also agrees with previous studies, where increased cytokines of Th1 response 56,57 and IP‐10 58 were also observed in CHC patients. Likewise, the increase in factors associated with SASP has also been observed in other viral infections such as hepatitis B 59 and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) 60 .…”
Section: Discussionsupporting
confidence: 91%
“…In particular, elevated concentrations of the proinflammatory cytokines IL-1β, IL-2, IL-6, IL-8, and TNF-α were found, cytokines that during normal healthy aging have been shown to be significantly increased compared with younger individuals (39,40). This also agrees with previous studies, where increased cytokines of Th1 response (41,42) and IP-10 (43) were also observed in CHC patients. Likewise, the increase in factors associated with SASP has also been observed in other viral infections such as Hepatitis B (44) and Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (45).…”
Section: Discussionsupporting
confidence: 91%
“…Peripheral blood mononuclear cells (PBMCs) were separated from fresh whole blood by density-gradient centrifugation on Ficoll-Hypaque (Pharmacia Biotech, Uppsala, Sweden) [24]. PBMCs were suspended at a final cell concentration of 8 × 10 6 cells/mL in Roswell Park Memorial Institute (RPMI) medium (Gibco BRL, New York, NY, USA) which contained 10% fetal bovine serum (FBS) (Eurobio Scientific, Scandinavie Les Ulis, France).…”
Section: Isolation Of Pbmcsmentioning
confidence: 99%